Performance analysis of hybrid Two-Stage Desiccant Cooling Cycle (Damascus University Journal for engineering sciences, 2024)
This research has studied hybrid two-stage desiccant cooling cycle, performance map of this cycle were drawn to compare this cycle and evaluate it with the conventional cycle easily. For the regeneration temperature equal to 60 ˚C, the energy consumption reduces from 22.48kw to 10.94kw, that’s equivalent to 51.3% and the cooling load on the cooling coil reduces from 63.157kw to 20.409kw, that’s equivalent to 67.7%. Moreover, EER increase from 0.826 to 1.695, that’s equivalent to 105.2%.
Keywords: Desiccant Wheel; Desiccant Cooling; Two Stage Desiccant; Energy Efficiency Ratio EER